2011
DOI: 10.1262/jrd.10-077t
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Detection in Putatively Unmated Mink (Mustela vison) by Serum Progesterone Level

Abstract: Abstract. The aim of this study was to determine whether blood plasma progesterone is a reliable indicator of pregnancy in mink at an early stage of gestation. We also attempted to establish the threshold value of progesterone as a pregnancy indicator. The analysis was carried out at a production farm on 42 standard female mink aged 1 year, which were grouped both according to the observed success of mating ("mated" and "unmated") and the level of blood serum progesterone measured afterwards ("pregnant" and "n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…This reasoning can be supported by the observations of Felska‐Błaszczyk et al . (), who found that more than 38% of putatively unmated female mink actually whelped; the workers had simply missed the copulation.…”
Section: Introductionmentioning
confidence: 99%
“…This reasoning can be supported by the observations of Felska‐Błaszczyk et al . (), who found that more than 38% of putatively unmated female mink actually whelped; the workers had simply missed the copulation.…”
Section: Introductionmentioning
confidence: 99%